PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PEMERINTAH KABUPATEN BULUKUMBA - Abdullah Abdullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
The Influence of Leadership Style, Organizational Culture,and Working Satisfaction on Employees’ Performance of Government of Bulukumba Regency. The aim of the research is to examine and analyze the Influence of Leadership Style, Organisational culture, and Working Satisfaction either partially or Simultaneously on officials’ Performance. The use of the variables is based on the previous results of researches,i.e. Yammarino et al (1993), Humphreys (2002), Bass (2003), Lund (2003), Mansur (2009), Mariam R. (2009). The research was conducted at Employment Agency and Regional Education and Training of Bulukumba Regency. The respondents consisted of 100 civil servant. the data were analyzed by using Faktor Analysis method with the help of SPSS program. Based on factor analysis, all indicators used in analyzing leadership style, Organizational Culture and Working Satisfaction are reasonable to be used for further analysis. The results of the research reveal that the factors of leadership style (X1), Organization culture (X2), and Working Satisfaction (X3) either partially and simultaneously have a positive and significant influence on officials’ performance (Y). Meanwhile, working satisfaction is the dominant variables affecting officials’ performance.